2016
DOI: 10.1097/md.0000000000004683
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics and clinical outcome of drug-induced liver injury in a Chinese hospital

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
8
0
2
Order By: Relevance
“…There were eight studies beyond the pseudo 95% confidence limits. Four of these that reported lower PPV were among studies with the largest sample sizes . The other four studies that reported higher PPV were studies with moderate sample sizes ranging from 130 to 688 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…There were eight studies beyond the pseudo 95% confidence limits. Four of these that reported lower PPV were among studies with the largest sample sizes . The other four studies that reported higher PPV were studies with moderate sample sizes ranging from 130 to 688 .…”
Section: Resultsmentioning
confidence: 94%
“…Studies from Asia or Australia were published in more recent years. Majority of the studies included adult populations (62%), two studies (7%) included children aged 18 years and below, eight studies (28%) included a mixed adult and children population, while age limit was not reported in one study . Apart from two prospective studies with shorter study periods, the rest of the studies were conducted retrospectively.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of patients with NAFLD (up to 70%) and ALD (up to 75%) experience significant functional impairment (including fatigue and cognitive difficulties) that affect activities of daily living and which persists over time . Fatigue is also a feature of drug‐induced liver injury (DILI), with approximately 40% of DILI experiencing clinically significant fatigue …”
Section: Fatigue In Liver Diseasementioning
confidence: 99%
“…19 Fatigue is also a feature of drug-induced liver injury (DILI), 26 with approximately 40% of DILI experiencing clinically significant fatigue. 27 These issues add significantly to the personal and societal burdens of these diseases and are an important driver of the indirect Terminology is also a significant issue with the word "fatigue" often meaning different things to different patients (and clinicians). Peripheral fatigue features can include a reduction in the degree or sustainability of suscle function.…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…Она более изучена при холестатических заболеваниях, при других -ее распространенность определена хуже. По отдельным данным, ГУ/С обнаруживается у 70% пациентов с неалкогольной жировой болезнью печени (НАЖБП), у 75% -с алкогольной болезнью печени, у 40% -с лекарственными поражениями печени (ЛПП) [8,9]. Этот симптом ухудшает качество жизни и повседневную деятельность при заболеваниях печени [10,11], негативно влияет на физическую активность (73%), семейную жизнь (57%) и работу (30%) [12].…”
unclassified